The antecedents of well‐being in first‐generation migrant children: A systematic review. Issue 3 (20th May 2021) - Bajo Marcos, Eva; Serrano, Inmaculada; Fernández García, Mª Mercedes
Abstract: Migrant children's well‐being has emerged into the spotlight of academic literature and policy‐makers in recent times. This systematic review is aimed at analysing the publication trends on the topic and at synthesising the available evidence on the antecedents of well‐being of first‐generation international migrant children. Systematic searches of primary studies were conducted in 18 databases using search terms related to migration, childhood and well‐being. Three rounds of screening and data extraction, researchers' full agreement and the inclusion criteria produced 39 eligible studies. Critical appraisal of results revealed a fragmentation in the literature, the evidence available being mostly descriptive and focused on involuntary migrants settled in Western countries. A bias across publications overlooking younger migrant children was unveiled. The compartmentalisation of the evidence hindered an understanding of the magnitude of the different effects of migration on well‐being. Antecedents of well‐being have been documented as factors fostering and hindering well‐being. Important gaps in literature and key antecedents of well‐being have been uncovered for voluntary and involuntary migrant children. These findings show limitations in the available evidence pointing to specific suggestions for future research that should help improve interventions at the social and individual levels.